How amylose molecular fine structure of rice starch affects functional properties. (15th January 2019) - Tao, Keyu; Li, Cheng; Yu, Wenwen; Gilbert, Robert G.; Li, Enpeng
Highlights: A new methodology shows amylose fine structure influences pasting & gelatinization. Peak and trough viscosities are increased by short and medium amylose chains. Peak, trough & setback viscosities are suppressed by long amylose chains. Molecular mechanisms are put forward to explain these new observations. Abstract: Starch molecular fine structure can have significant effects on pasting and thermal properties of rice flour. This study investigates the mechanistic explanation of these effects, by obtaining data for rice flour with different starch fine structures. Starch structural parameters for both amylose and amylopectin were obtained using size-exclusion chromatography (SEC, a type of gel-permeation chromatography, GPC), and the data fitted with methodologies (one of which is new) based on the underlying biosynthetic processes. It is found that the setback viscosity of rice starch measured by the rapid viscosity analyzer (RVA) depends not only on amylose content but also on the amount of long amylose chains and the size of whole amylopectin molecules. Conversely, long amylose chains and large amylopectin molecules are found to be responsible for the lower peak and trough viscosities. Other results for the effects of amylopectin chains are consistent with the literature. Mechanistic explanations for all observations are put forward. The novel findings about the influence of the distribution of amylose chain lengths and whole amylopectin size, in addition to amylose content alone, can provide guidance for rice breeders and food scientists in the selection of rices with improved functional properties.